Incremental Strength Gain Considerations in Staged Roadway Construction - Dario Rosidi (Civil Engineering Dimension, 2022)
This paper presents an alternative construction method of a highway along coastal area underlain by thick normally consolidated very soft organic clay. Due to its remote location, mitigations to strengthen the soft clay are deemed too costly and/or require significant time to mobilize. Without mitigations, the presence of this very soft clay necessitates the roadway embankment to be constructed in phases to allow partial consolidation of clayey soils to take place before additional embankment fill can be placed. At each construction phase, the additional fill thickness and staging time are determined, and the corresponding degrees of consolidation and incremental strength gains are calculated at discrete grid points within the soft organic clay. The stability of the partially built embankment is then evaluated, and the fill thickness and staging time are adjusted to meet the stability safety requirements. The settlement due to fill placement can be estimated at each construction phase and included as an overbuilt to the next fill placement thickness. Impacts of soil horizontal and vertical movements due to filling to pile foundations are also be discussed.